Application of Criminal Sanctions Law Against Debt Collectors Withdrawing Fiduciary Guarantee Objects - Nur, Rafika; Gobel, Rongki Ali; Sumiyati, Sumiyati; Abbas, Zilfinaz (Universitas Negeri Gorontalo, 2024)
This study examines the application of criminal sanctions to debt collectors involved in withdrawing fiduciary guarantee objects, focusing on their actions in executing such guarantees under Financial Services Authority Regulation No. 35 of 2018. Employing empirical legal research and field data, the study identifies that debt collectors who use excessive methods in seizing fiduciary objects may be liable for criminal acts, particularly under Article 368(1) of the Criminal Code, which covers extortion. The novelty of this research lies in its detailed analysis of the legal implications surrounding debt collector behaviour during fiduciary executions. The findings clarify the legal boundaries and potential sanctions for violations, underscoring the need for stricter enforcement of laws governing debt collection practices. The study recommends stronger legal oversight and the implementation of clearer regulations to ensure debt collectors act within legal and ethical boundaries. Furthermore, the research calls for enhanced public awareness of legal protections for debtors and more rigorous oversight to prevent abusive debt collection practices.